The Association between the Duration of Preoperative Pain and Pain Improvement in Vertebral Augmentation: A Meta-Analysis - Ehteshami Rad, A.; Luetmer, M.T.; Murad, M.H.; Kallmes, D.F. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Most physicians consider length of preoperative pain as an important factor to include patients for SA. Our aim was to synthesize the available evidence regarding the influence of preprocedural pain duration on the outcome of vertebral augmentation procedures. MATERIALS AND METHODS: The MEDLINE data base was reviewed up to March 2010. Meta-regression and mixed-effect subgroup analyses were performed to evaluate the association between the outcome of interest, which was pain improvement assessed by a VAS (0–10) and the duration of preoperative pain (independent variable). RESULTS: We included 17 articles. The mean VAS improvements for subgroups of ≤6 weeks (n = 12), 6–24 weeks (n = 5), and >24 weeks (n = 3) were 5.18, 4.90, and 5.04, respectively (P = .86). The regression coefficient was −0.024, suggesting trivial association of the duration of preoperative pain and pain improvement. CONCLUSIONS: Pain relief following spine augmentation was similar among groups of patients with varying lengths of preoperative pain duration. KPkyphoplastyNAnot applicableSAspine augmentationVASvisual analog scaleVPvertebroplasty